MASJID, PERAN SOSIAL, DAN PEMBERDAYAAN MASYARAKAT (OPTIMALISASI PERAN MASJID DARUSSALAM KEDUNGALAR NGAWI RESPONSIF PENDIDIKAN ANAK) - Ulfa Masamah (Institut Islam Mamba'ul 'Ulum Surakarta, 2020)
The most important function of the mosque is as a place to carry out the prayer in congregation, but also as a basis for community empowerment, as the Darussalam mosque at Kedunggalar Ngawi. This study aims to describe the experience of community empowerment through the Darussalam mosque and the impacts arising from such empowerment. This research uses the sociology of religion approach. This type of research is descriptive qualitative. Data collection is done by observation, interview and documentation. While the data analysistechnique uses interactive analysis which includes data reuction, data display, and conclusions. The results of this study are the administrators and takmir of the Darussalam mosque to empower the community through the Darussalam mosque aspects or the education sector. The education sector includes Madrasah Diniyah (TPQ) Darussalam, Raudhotul Athfal (RA) Darussalam, Madrasah Ibtidaiyah (MI) Darussalam, MTs Darussalam, and MA Darussalam Kedunggalar. With the empowerment of these communities, benefits can be felt and improve people’s welfare in their lives.